(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Online learning during the period of quarantine restrictions greatly influenced the learning ability and motivation of students, the direction of training and the course of which is strongly related to the practical testing of acquired knowledge. For this reason, to compensate for the negative impact, additional incentive measures and special tools are needed to ensure the connection of theory with practice at the level of visual, conceptual and tactile perception. This work is devoted to the consideration of distance learning methods and tools applicable to ensure the connection between theory and practice in the human anatomy and physiology course for students [1,2,5,6]